Turning students into science stars (science and engineering education). - Cocozza, J.D.
To meet the demands for greater numbers of biomedical engineers, it is necessary to expand the biomedical engineering and related educational programs in the United States to provide students with a focused exposure to basic science, engineering, and technology development principles central to advances in this industry. Over the past 30 years, however, the United States has seen a precipitous decline in the number of American students studying science and engineering. It is this downward spiral the Biomimetic Microelectronic Systems Engineering Research Center (BMES ERC) Education Outreach Program seeks to address. This program affects the science literacy of more than 2,000 minority and economically disadvantaged Los Angeles Unified School District students and their teachers each year. In addition, the BMES ERC has augmented the course curricula of undergraduate and graduate students. All facets of the program are facilitated by experience-dependent mentoring throughout the entire curriculum, using BMES ERC testbeds and thrusts research as focal points of learning and motivation. Through its outreach program, BMES ERC scientists and engineers transfer the excitement, knowledge, and skills generated by their research to students from grade school to graduate school.
Keywords: Biomimetic Microelectronic Systems Engineering Research Center Education Outreach Program; United States; Biomedical engineering; Engineering education; Experience-dependent mentoring; Science education